Testing Building Fabric Performance and the Impacts Upon Occupant Safety, Energy Use and Carbon Inefficiencies in Dwellings. (December 2015) - Littlewood, J.R.; Smallwood, I.
Abstract: Building fabric efficiency is a central tenet to increasing thermal performance and decreasing carbon emissions of domestic dwellings, promoted within the UK Government Zero Carbon homes policy framework. Increasing demands in the Design and Construction of building fabric efficiencies is driven by increasing stringent regulations and standards. Yet, in reality there is increasing evidence of a 'Performance Gap' between the design intents and the as-built constructed building fabric, such that some new dwellings inherit inefficiencies from the construction process. The presence of construction issues including thermal bridging, discrepancy in 'U' values and increases in air permeability contribute to increased heat loss and carbon emissions and thereby, decreasing energy and carbon efficiency. Equally, building fabric weaknesses can also contribute to the overall building performance compliance for mandatory smoke and fire spread mitigation. This paper presents three case-studies involving independent testing and performance evaluation undertaken on social housing dwellings within South Wales, UK. The paper provides further evidence to support the rationale for standardization of diagnostic testing during the construction stages of dwellings, adding to the body of evidence for in-construction testing (iCT) developed by Cardiff Metropolitan University, to reduce instances of the performance gap and its impacts upon occupant comfort, energy costs and carbon emissions.